Photocatalytic degradation of methylene blue by Zn2SnO4-SnO2system under UV visible radiation - Patcharanan Junploy (2018)
© 2017 Elsevier Ltd Zn2SnO4-SnO2system was successfully synthesized by co-precipitation under ultrasonic radiation combined with high temperature calcination. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, fluorescence spectroscopy and UV–visible absorption spectroscopy revealed the presence of cubic particles mixed with nanoparticles of Zn2SnO4-SnO2composites which were synthesized from Zn:Sn molar ratios of 1:1 and 3:2. Upon using Zn:Sn molar ratios of 3:1 and 2:1, additional ZnO minor phase was detected. In addition, the calculated pseudo-first-order rate constant of the product synthesized from 3:2 molar ratio of Zn:Sn was the highest at 12.244×10–3 min–1.